Pareto Tracer: a predictor–corrector method for multi-objective optimization problems. Issue 3 (4th March 2018) - Martín, Adanay; Schütze, Oliver
ABSTRACT: This article proposes a novel predictor–corrector (PC) method for the numerical treatment of multi-objective optimization problems (MOPs). The algorithm, Pareto Tracer (PT), is capable of performing a continuation along the set of (local) solutions of a given MOP with k objectives, and can cope with equality and box constraints. Additionally, the first steps towards a method that manages general inequality constraints are also introduced. The properties of PT are first discussed theoretically and later numerically on several examples.